2016
DOI: 10.1159/000449283
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Behavioural Changes, Cognitive Symptoms, and Functional Disability in Primary Progressive Aphasia: A Longitudinal Study

Abstract: Background: The contribution of behavioural changes to functional decline is yet to be explored in primary progressive aphasia (PPA). Objectives: (1) investigate functional changes in two PPA variants [semantic (svPPA) and non-fluent (nfvPPA)], at baseline and after 12 months; (2) investigate baseline differences in behavioural changes between groups, and (3) explore predictors of functional decline after a 12-month period. Methods: A longitudinal study involving 29 people with PPA (18 svPPA; 11 nfvPPA) seen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…The bvFTD group had on average higher severity levels (mean = 6.5) based on the CDR ratings than people with AD-dementia (mean =4.2, p<0.001). Chi-square tests showed significant differences across ethnicity (c 2 (1)=30.5, p<0.001), gender (c 2 (1) =40.5, p<.001), and marital status (c 2 (1)=48.39, p<0.001), with a larger proportion of people with bvFTD being male (64.7%; AD-dementia=45.6%), white (bvFTD=93.7%; AD-dementia=80.8%), and married (bvFTD=86.3%; AD-dementia=68.7%). Table 2 shows the number of people with assessment data at different visits for each patient group.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bvFTD group had on average higher severity levels (mean = 6.5) based on the CDR ratings than people with AD-dementia (mean =4.2, p<0.001). Chi-square tests showed significant differences across ethnicity (c 2 (1)=30.5, p<0.001), gender (c 2 (1) =40.5, p<.001), and marital status (c 2 (1)=48.39, p<0.001), with a larger proportion of people with bvFTD being male (64.7%; AD-dementia=45.6%), white (bvFTD=93.7%; AD-dementia=80.8%), and married (bvFTD=86.3%; AD-dementia=68.7%). Table 2 shows the number of people with assessment data at different visits for each patient group.…”
Section: Demographicsmentioning
confidence: 99%
“…In particular, only PNFA patients were reported to have a significant deterioration in total ADL and total IADL functioning over 12 months. In two recent studies similarly focusing on FTD syndromes, O'Connor et al 2 reported similar levels of everyday functioning decline between semantic and non-fluent variant of primary progressive aphasia patients over five years, whilst in a separate analysis bvFTD patients were found to show faster levels of IADL decline 19 . These studies provide some important first insights, however, to existing knowledge, no study to date has compared individual IADL functioning across bvFTD and AD over a prolonged period of time.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Three clinical subtypes are generally recognised: behavioural variant frontotemoral dementia and two primary progressive aphasias, semantic variant and non-fluent variant. These FTD subtypes present differently in the early stages, and while all experience progressive declines, the patterns of cognitive, behavioural and functional decline differ [1][2][3][4]. The impact of FTD is not limited to the person diagnosed with dementia but also affects the informal carers.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the prior work has focused on bvFTD, which in some [4,5] but not all [6–9] studies produces more profound functional deficits than Alzheimer’s disease (AD). A subset of reports have also included svPPA and/or nfvPPA [4,5,7,1012] and generally concluded that ADL performance, particularly for basic ADLs, is also poorer in bvFTD than in these other clinical FTD subtypes. However, due to the relatively smaller sizes of FTD cohorts at individual research centers, it remains uncertain whether these clinical FTD subtypes differ in their patterns of functional impairment as well as in their overall severity [4,7].…”
Section: Introductionmentioning
confidence: 99%